Diffuse lipomatosis of the thyroid gland with papillary microcarcinoma: Report of a rare entity - Hariharanadha Sarma Nandyala; Srinivasulu Madapuram; Megha Yadav; Sudheer Kumar Katamala (Wolters Kluwer Medknow Publications, 2015)
Presence of lobules of adipose tissue either focally or diffusely is very rare in the thyroid gland. Fat accumulation can be macroscopic or microscopic. Focal infiltrates of fat have been reported in conditions such as adenolipoma, intrathyroid lipoma, and encapsulated papillary carcinoma. Diffuse lipomatosis has been reported in conditions such as amyloid goitre, heterotopic fat nests, thyrolipoma and liposarcoma. The exact mechanism of fat accumulation is not known although there are many theories postulated. Investigations such as ultrasound, computed tomography scan, and magnetic resonance imaging can detect the presence of macroscopic fat in the thyroid gland. Accurate diagnosis of the type of fat accumulation is necessary because tumorous and nontumorous conditions fall into the differential diagnosis. Only nine cases of papillary carcinoma associated with lipomatosis of thyroid are reported so far. We report possibly the first case of diffuse lipomatosis of the thyroid gland with a focus of papillary microcarcinoma.